Material Requirements Planning (MRP) in the Implementation of Minimarket Inventory Stock Control - Rila Fauziah; Muhammad Nandy Pinto; Lusiana Lusiana (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
Inventory control is a key to operational success in minimarket retail. This study examines the effectiveness of the Material Requirements Planning (MRP) method adapted from manufacturing to retail inventory systems. Through quantitative simulation, the Master Production Schedule was adjusted into a Master Procurement Schedule based on Point of Sale data. MRP computation proved effective in balancing shelf inventory on a Just-in-Time basis. Results indicate a reduction in stockouts to below 2%, an increase in inventory turnover, and holding cost efficiencies of up to 35%. This implementation successfully optimizes minimarket working capital turnover efficiently.